EFFECT OF ADDITIVES ON VARIOUS SPERMATOZOAL ATTRIBUTES OF FRESH, FROZEN-THAWED AND REFRIGERATED SEMEN - RAVAL, RUPESH J; DHAMI, A J (The Indian Journal of Animal Reproduction, 2023)
Thirty six ejaculates from 4 mature triple crossbred (25% HF x 25% J x 50% Kankrej) bulls were spli1 into 3 aliquots each and were processed for freezing and refrigeration storage in TFYG diluent without and with EDTA(0.1 %) or Cysteine HCI (0,1%). The percentages of motile and live sperm and intact acrosome were significantly (P < 0.01) higher in presence of EDTA and/or cysteine as compared to control Tris diluent at all steps of semen processing/ preservation. Further, the motile sperms at initial, prefreeze, post-thaw and post-refrigeration stages were highly significantly (P < 0.01) interrelated (r = 0.35 to 0.88), and so also were the cases for iive sperm (0.26 to 0. 76), abnormal sperm 0.20 to 0.62) and intact acrosome (0.30 to 0.76). Moreover, the sperm motility at different steps of semen processing/preservation had significant (P<0.05) positive correlations with post-thaw and postrefrigeration live sperm (0.21 to 0.30), negative correlations with prefreeze and post-refrigeration abnormal sperm (-0.19 to-0.32) and highly significant positive correlations with intact acrosome at all steps of semen processing/preservation (0.19 to 0.39). Similarly, live sperm percent at different steps of semen processing/preservation had significant negative correlations with abnormal sperm (0.19 to 0.43) and positive correlations with intact acrosome (-0.20 to-0.39), except that the initial and post-refrigerated live sperm did not reveal significant relation with intact acrosome at initial, prefreeze and post-thaw stages, whereas abnormal sperm at different steps of semen processing/preservation had significant negative correlations with intact acrosome particularly at initial and pr freeze stages (-0.20 to-0.34). These correlations suggested that the assessment of motile, live and abnormal sperm and intact acrosome could be of practical utility in routine semen evaluation to predict its keeping quality and freezability in triple crossbred bulls, and that only the motility, which is a very simple rapid and subjective way of assessment, could serve the purpose of more tedious and time consuming staining procedures in routi_ne semen analysis to predict its quality.